Evaluation of different types of isolation techniques in dentistry - Overview - Priyanka Sivasubramanian, Dr. Rajasekar G, (Cuestiones de Fisioterapia, 2023)
Background: In dentistry, it is well known that the main cause of procedure failure is inadequate tooth isolation. Even though it’s been a staple of modern dentistry for decades, isolation remains a pesky but critical step particularly in endodontic and restorative procedures. It’s not just one aspect of isolation that makes it difficult but tooth isolation by nature isn’t easy, specifically when you add in the patient’s comfort, it can be a challenging task. Any operative procedure needs adequate space over the operating field. There must be proper control of moisture, good accessibility and visibility as well as spacious for instrumentation around the working area. For easy manipulation this kind of environment is necessary. The aim of this review is to evaluate the different types of isolation techniques in dentistry.